Supplementation of okra seed oil ameliorates ethanol-induced liver injury and modulates gut microbiota dysbiosis in mice. Issue 10 (12th September 2019) - Zhang, Jin; Lu, Yalong; Yang, Xingbin; Zhao, Yan
Abstract : This study assesses the possible effects of dietary okra seed oil (OSO) consumption on attenuation of alcohol-induced liver damage and gut microbiota dysbiosis, and associated mechanisms in mice. Abstract : This aim of this study is to assess the possible effects of dietary okra seed oil (OSO) consumption on attenuation of alcohol-induced liver damage and gut microbiota dysbiosis, and associated mechanisms in mice. Mice were orally administered alcohol alone or in combination with OSO at 400 and 800 mg per kg bw for 8 weeks. OSO caused a strong inhibition of abnormal weight loss and liver fat accumulation in alcohol-administered mice. Malonaldehyde production was also effectively antagonized, and glutathione peroxidase and superoxide dismutase activities were elevated by OSO treatment in ethanol-based mice ( p < 0.05). Concentrations of hepatic TNF-α, IL-1 and IL-6 were decreased after OSO treatment when compared with alcohol-treated mice, respectively ( p < 0.05). As revealed by 16S rDNA gene sequence analysis, OSO notably reduced the Proteobacteria proportion and enhanced the Bacteroidetes population of alcohol-treated mice, and a significant reduction in Clostridium XlVa and Staphylococcus was observed, revealing that OSO attenuated the alcohol-induced gut dysbiosis. OSO also attenuated lipid metabolic disorder by modulating metabolism of serum free fatty acids in ethanol-based mice, but had no significant difference in cecum total short-chain fatty acids among the tested mice. Amelioration of these parameters and liver injury via H&E staining examination demonstrated that OSO consumption could effectively protect against liver damage and maintain intestinal eubiosis in mice.